A Review of High-Temperature and High-Pressure Experimental Apparatus Capable of Generating Differential Stress - Ren, Dongsheng; Li, Heping (Frontiers in Earth Science, 2022)
Currently, high temperature and high pressure experimental set-up that can be used to simulate temperature, hydrostatic pressure, and differential stress in the Earth's interior includes the Griggs press, Paterson rheometer, D-DIA press, RDA press, and torsional diamond anvil cell. Nevertheless, the maximum hydrostatic pressure that can be simulated in Griggs press under high temperature is only about 2 GPa, and there is a large uncertainty in the calibration of differential stress; the Paterson rheometer provides too low confining pressure; the D-DIA and RDA press can simulate a wide range of temperature pressures, but the D-DIA can achieve very small strain variables; the RDA press has very heterogeneous sample stresses; the torsional diamond anvil cell has a small sample size, and it is difficult to calibrate the differential stress. Additionally, these existing high temperature and high pressure experimental set-up with differential stress are not easily interfaced with in-situ measurement systems for physical properties such as electrical, ultrasonic and thermophysical properties. Hence, scholars need to invest more efforts in the research and development of high temperature and high pressure set-up with differential stress in the future to properly understand the composition, structure, configuration, properties, and interactions of the matter in the Earth's interior.